Working with the Sketch prototyping tool (Infinite Skills, 2017)
"Sketch is a software tool built for one specific purpose: to give you the power to rapidly create visually stunning representations - prototypes - of the web sites and apps you want to build; which you can then share with other people. In this course, design pro Andy Anderson takes you through the entire start-to-finish process of using Sketch to construct and export a real-world prototype of a mobile phone app. He starts with the basics of the Sketch app by getting you familiar with the interface, then teaches you to import assets into the work area, and shows you how to create and manipulate objects. He also advises you on efficient ways to organize and plan your projects, and finishes by explaining the best ways to export the finished product so you can share it locally or over the Internet."--Resource description page